INFORMATION SUPPORT OF THE INTERNET-STORE ON THE SOCIAL NETWORK INSTAGRAM - FEDUSHKO, SOLOMIIA; BUCHII, NATALIIA; SYEROV, YURIY (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article analyzes the internet-store on the social network Instagram. Today, social networks have rapidly entered not only people's lives, but also play an important role in entrepreneurship and have become an effective method of implementing any business projects. One of the most popular social platforms is Instagram. This social network allows entrepreneurs to promote their products on the Internet, having a real business. The main task in such promotion is the correct choice of the target audience and the presence of a clear content plan.Designing and maintaining a page on the social network is a profitable solution for small businesses. The development of the site is necessary for the global network, and for the cosmetics store a profitable addition to the business will be a page on the social network Instagram. The social network Instagram will help increase the target audience of the store and the sale of goods in general. The object of research is the activity of cosmetic stores on the Internet. The subject of research is information support for the activities of the internet-store «Beauty Island» on the social network Instagram.Researchers consider the corporate profile in social networks as a profile that is a necessary tool for the effective operation of any organization. Maintaining a page on social networks allows you to connect with the target audience and improve communication with it.There are two concepts of marketing: e-marketing and internet marketing. E-marketing is a social process that focuses on the need to satisfy consumers on the Internet, creates an offer and exchanges services / goods, using information and communication technologies. The concept of Internet marketing is considered as a construction of marketing communications via the Internet. This is not a completely independent field, but just a marketing tool that has its own characteristics.The results of the work a developed internet-store «Beauty Island» on Instagram, which is used to find a new target audience and increase sales of the store «Beauty Island». Improved promotion methods can be used for the effective operation of the internet--store.
Keywords: internet-store; social network; promotion; internet marketing; online commerce